Extended plasticity in commercial-purity zinc - Williams, D. A. C.; Naziri, H.; Pearce, R. (College of Aeronautics, 1968)
90% rolling-reduction of annealed commercial-purity zinc sheet (grain size 100 - 150 μ) results in the fragmentation of the large grains into, finally, stable micro-grains, 1 - 211 in diameter. The stability of the micro-grains is due to the presence of soluble and insoluble impurities which prevent recrystallization. This micro-grain material is strain-rate sensitive, and elongations of 200% have been obtained at room temperature. Although this as-rolled, 90% reduction zinc sheet is not super-plastic according to the current definition, its behaviour has led to the coining of the phase 'extended plasticity'. Evidence of grain-boundary sliding is found on examination of the surface by scanning electron microscopy, while the examination of thin foils and activation energy measurements support the dynamic softening (recovery) theory; thus, both these mechanisms must be operating, to a greater or less extent, to confer on this material the observe mechanical behaviour. It is finally concluded that it is dangerous to draw conclusions regarding the mechanism of plastic deformation from surface observations alone.